Evaluating the effect of vitamin D3 fortification on physicochemical and sensory properties of yogurt - Saneela Saleem; Zahra Khan; Imtiaz Hussain; Faran Khan; Fahad Al-Asmari; Faima Atta Khan; Alyan Ali Zafar; Muhammad Abdul Rahim; Zongo Eliasse; Mohamed Fawzy Ramadan (Cogent Food & Agriculture)
More than one billion people around the globe are suffering from severe to moderate vitamin D deficiency. In Pakistan, 53.5% people suffer from vitamin D deficiency. The purpose of this study is to develop vitamin D fortified yogurt with two varying concentrations of vitamin D3, aiming to observe how these concentrations impact the physicochemical and sensory characteristics of the fortified products. A total of 750 mL of pasteurized milk was divided into three equal batches. For T1 and T2, 50 µL and 66.67 µL of emulsified vitamin D3 were added at 50 °C, respectively. Yogurt samples were prepared in triplicates and underwent storage tests, including proximate analysis, pH, viscosity, and vitamin D3 stability at 4 ± 1 °C. During the first week of storage, the viscosity of yogurt increased but later it started decreasing because of syneresis. T1 (8.1) and T2 (8.2) obtained a better overall sensory score using a 9-point hedonic scale as compared to T1 (7.9) During the 28-day storage period, the vitamin D3 content significantly decreased (P < 0.05) in T1 and T2. By the end of the 28-day period, in T1 and T2, the vitamin D3 content decreased from 15.0 and 20.32 to 13.78 and 17.67 respectively. The results of the current study demonstrate that the fortification of yogurt with vitamin D3had no detrimental effect on the physicochemical as well as the organoleptic properties of yogurt. Although the vitamin D3 content decreased during storage, it could be preserved if fortified yogurt is stored in opaque containers.